ShearWave™ Elastography BE1 Multinational Breast Study: Additional SWE™ Features Support Potential to Downgrade BI-RADS®-3 Lesions - Schäfer, F. K. W.; Hooley, R. J.; Ohlinger, R.; Hahne, U.; Madjar, H.; Svensson, W. E.; Balu-Maestro, C.; Juhan, V.; Athanasiou, A.; Mundinger, A.; Order, B.; Locatelli, M.; Cosgrove, D.; Wolf, O. J.; Henry, J. P.; Moutfi, M.; Gay, J. M.; Cohen-Bacrie, C. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: To determine the benefit of ShearWave™ Elastography (SWE™) in the ultrasound characterization of BI-RADS® 3 breast lesions in a diagnostic population.Materials and Methods: 303 BI-RADS® 3 lesions (mean size: 13.2 mm, SD: 7.5 mm) from the multicenter BE1 prospective study population were analyzed: 201 (66 %) had cytology or core biopsy, and the remaining 102 had a minimum follow-up of one year; 8 (2.6 %) were malignant. 7 SWE features were evaluated with regard to their ability to downgrade benign BI-RADS® 3 masses. The performance of each SWE feature was assessed by evaluating the number of lesions correctly reclassified and the impact on cancer rates within the new BI-RADS® 3‘ lesion group. Results: No malignancies were found with an E-color “black to dark blue”, which allowed the downgrading of 110/303 benign masses (p < 0.0001), with a non-significant increase in BI-RADS® 3‘ malignancy rate from 2.6 % to 4.1 %. E-max ≤ 20kPa (2.6 m/s) was able to downgrade 48/303 (p < 0.0001) lesions with a lower increase in BI-RADS® 3‘ malignancy rate (3.1 %). No other SWE features were useful for reclassifying benign BI-RADS® 3 lesions.Conclusion: Applying simple reclassification rules, SWE assessment of the maximum stiffness of lesions allowed the downgrading of a sub-group of benign BI-RADS® 3 lesions. This was accompanied by a non-significant increase in the malignancy rate in the new BI-RADS® 3 class.
Keywords: breast; ultrasound; diagnostic radiology; tumor